Pendampingan Pembuat Perangkat Pembelajaran Berbasis Digital Di SDN 2 Girimoyo Kabupaten Malang - Kusumaningtyas, Dian Ika; Nuro, Falistya Roisatul Mar'atin (Forum Kerjasama Pendidikan Tinggi, 2023)
The background of this community service activity is because not many teachers have made digital-based learning tools. Based on the socialization carried out in partner schools, some teachers are still confused about making digital-based learning tools. However, some teachers are also equipped with facilities that support the achievement of making learning devices which is the teacher's job in providing the best teaching for students. This community service aims to provide training to teachers at SDN Girimoyo 2 Malang in the form of making digital-based learning tools. This training was carried out using lecture methods, outreach, question and answer discussions and assistance in making learning tools. This community service activity consisted of 3 meetings in 1 partner school. The output achieved in this partnership program is an increase in the competence of teachers at SDN 2 Girimoyo Malang manifested in the ability to make digital-based learning tools. In addition, training material was also produced in the form of drafts for making digital-based learning tools, RPP (Learning Implementation Plans) and LKPD (Student Worksheets).